Have a Free Video Meeting with one of our friendly tutors.

I would first isolate x in the first equation in the left hand side (x = 2 + 2y). Then I would replace the x in the second equation with the right hand side of the first equation, making the second equati...

2(x^{2}) - 2x - 12= 2( x^2 - x - 6)The constant is negative so the 2 factors must have opposite signs. Then, the x term is negative so the larger one must be negative, and the smaller one positive...

4(2x + y) = 11 + 7y expand the brackets8x + 4y = 11 + 7y move +4y to the other side8x = 11 + 3y move 8 to the other sidex= (11 + 3y)/8

If y=x^2 + ax + b is the equation for the curve, then the points which lie on the curve must satisfy this equation.Inputing the points into the equation gives:-4 =6^2+6a+b -6=4^2+4a+bNow solve simultaneou...

I will explain best during the interview on the whiteboard space